Reinforcement History Dependent Effects of Low Dose Ethanol on Reward Motivation in Male and Female Mice - Bryant, Kathleen G.; Singh, Binay; Barker, Jacqueline M. (Frontiers in Behavioral Neuroscience, 2022)
Alcohol use disorders (AUDs) are more prevalent in men than in women, though AUD diagnoses in women are growing rapidly, making an understanding of sex differences in alcohol-related behaviors increasingly important. The development of AUDs involves the transition from casual, low levels of alcohol drinking to higher, maladaptive levels. The ability of low dose alcohol to drive reward and drug seeking may differ in males and females, and this could underlie differences in susceptibility to AUD. In this study we sought to determine whether a history of chronic, low dose ethanol exposure (0.5 g/kg; i.p.) could drive sucrose reward seeking and motivation, and whether this differed between male and female mice. Adult mice were trained to lever press for a liquid sucrose reward on two reinforcement schedules: a random interval (RI) schedule and a variable ratio (VR) schedule. After training, mice were tested on each of these levers for reward motivation using a progressive ratio test. We found that a history of low dose ethanol exposure increased sucrose reward motivation in male mice, but only on the RI lever and only when exposure occurred proximal to learning. Female mice were more motivated for sucrose on the RI lever than the VR lever regardless of ethanol exposure condition. These findings indicate that training on different reinforcement schedules affects reward motivation. Further, we show that males are more susceptible to the effects of low dose ethanol on sucrose reward motivation than females. These data broaden our understanding of sex differences in reward seeking as a result of ethanol exposure.